Belgium : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2001 Article IV Consultation highlights that following four years of robust expansion, real GDP growth in Belgium slowed markedly in 2001, as higher oil prices, declining equity values, and the deteriorating external environment adversely affected business investment, household consumption, and exports. The outlook for 2002 depends critically on a recovery in the world economy and, especially, in Belgium's key European trading partners. Growth for the year is projected by the IMF staff at 0.7 percent, although activity is expected to pick up significantly in the second half of the year.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet